The Role of Minimally Invasive Surgery in the Treatment of Lung Metastases. (4th March 2017) - Guerrini, Gian Piero; Lo Faso, Felice; Vagliasindi, Alessio; Lembo, Rosalba; Solaini, Luciano; Soliani, Paolo; Taviani, Mario; Porrello, Calogero
ABSTRACT: Introduction : The ideal surgical approach for pulmonary metastasectomy remains controversial. Thoracoscopic surgery may offer advantages in quality of life outcomes, with equivalent oncologic long-term results. This study aimed to demonstrate the validity of video-assisted thoracoscopic surgery (VATS) in the treatment of lung metastases. Methods : In all 224 patients who underwent 300 VATS metastasectomies from January 2000 to December 2013 were retrospectively reviewed. Sixty-nine patients underwent major resection (68 thoracoscopic lobectomies and one pneumonectomy) and 155 patients underwent a wedge resection/segmentectomy. Complete curative pulmonary resections were performed in 219 (97%) cases. The Kaplan–Meier method was used to estimate survival curves. Univariate and subsequent multivariate Cox model regression were performed to identify independent factors of overall survival. Results : One hundred eighty-six patients developed lung metastases from epithelial tumors, 28 from sarcomas, seven from melanomas, and three from germ cell tumors. The final pathological examination revealed no cases of R1 disease. After a mean follow-up of 40 months, 118 patients (53%) had died. According to a multivariate analysis, a better prognosis was not observed for patients with a particular histological type; in addition, disease-free interval time, age, number of metastases, and type of surgery did not have any statistical influence on long-term survival. Conclusions : Thoracoscopic surgery is a safe and efficacious procedure, with a five-year overall survival that is equivalent to open surgery.